Village Head’s Leadership Style to Improve Village Development: Study on Durian Village, Padang Cermin District, Pesawaran Regency - Putri, Martharia; Suryani, Eny Inti; Wati, Yonna; Warsiyah, Warsiyah (Pancasila International Journal of Applied Social Science, 2025)
The village government has the main obligation to carry out physical development in order to improve the welfare of the village community. The role of the village head as a leader greatly determines the success of development, especially in creating equity and encouraging community participation. This study aims to analyze the leadership style of the Head of Durian Village, Padang Cermin District, Pesawaran Regency, in improving the physical development of the village in 2021. The research used a qualitative approach with data collection techniques through interviews with nine informants consisting of village officials and communities. The results of the study show that the leadership style applied tends to be participatory, shown by the involvement of the community in village development planning deliberations (Musrenbang) and direct communication between village heads and residents. However, the application of this participatory style is not optimal because there is still a development gap between hamlets, especially between the more advanced Tegal Arum Hamlet and the underdeveloped Pakuan Hamlet. Low levels of awareness, differences in education and economic conditions, and the apathy of the community are also obstacles to participation. The conclusion of this study confirms that although participatory leadership has been sought, its effectiveness is still limited and has not been able to evenly distribute development as a whole. The implication of these findings is the need for a more adaptive, communicative, and inclusive leadership strategy so that community participation can increase and village development can run more evenly and sustainably.